2000
DOI: 10.3719/weed.45.96
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Amino Acids and Glycinebetaine by NaCl Treatment and its Relation to Salt Tolerance in Three Gramineous Plants.

Abstract: Abstract:Two gramineous weeds, early watergrass (Echinochloa wyzicola Vasing) and foxtail (Setaria viridis (L.) Beauv.), and rice (Oryza sativa L. cv. Nipponbare) were exposed to salinity stress. The leaf water status, levels of amino acid, proline, and glycinebetaine of seedlings during the 7 days following root treatment of 50 and 100mMNaCI were measured. Foxtail and early watergrass were able to maintain a high turgor and high relative water content under the salinity condition. Proline content in leaves wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Proline was the most abundant amino acid that increased with NaCl treatment in the plants. This amino acid is considered one of the compatible solutes which accumulates in the cells and maintains the osmotic balance between the cells and the outer environment (Venkatesan & Chellappan 1998; Kim et al . 2000; Jain et al .…”
Section: Resultsmentioning
confidence: 99%
“…Proline was the most abundant amino acid that increased with NaCl treatment in the plants. This amino acid is considered one of the compatible solutes which accumulates in the cells and maintains the osmotic balance between the cells and the outer environment (Venkatesan & Chellappan 1998; Kim et al . 2000; Jain et al .…”
Section: Resultsmentioning
confidence: 99%
“…This result showed that these antioxidant enzymes acting as the scavenging system might not greatly contribute to salt tolerance mechanism in E. oryzicola. Kim et al (2000) suggested that reduction of Na absorption and translocation, and accumulation of glycinebetaine and proline might contribute more to its salt tolerance than oxidative scavenging system in E. oryzicola.…”
Section: Discussionmentioning
confidence: 98%
“…Salt tolerance of some gramineous weeds, early watergrass ( Echinochloa oryzacola Vasing) and foxtail ( Setaria viridis (L.) Beauv. ), was related to osmotic adjustment to saline stress with accumulation of proline and glycinebetaine (Kim et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2000). However, most of the research related to salt stress or salt tolerance has mainly been carried out in crops or halophytes, and little information is available regarding the salt tolerance of the glycophyte weeds (Flores 1985; Greenway & Munn 1980; Kim et al . 1999, 2000).…”
Section: Introductionmentioning
confidence: 99%